Determination of levels of gaseous air pollutants emitted at Ajakanga dump site, Ibadan, Nigeria - AYODEJI, FALUSI, BAMIDELE; AJIBIKE, ODEDOKUN, OMOBOLA; ADIKETU, ABUBAKAR,; TUNDE, BOLARINWA, OLADAYO; EGBE, AGBIKE, JOHN (IJRDO-Journal of Applied Science, 2017)
Municipal solid waste dump sites have been reported to generate different kinds of air pollutants the world over. Air pollutants, such as CO, H2S, NH3, NOx and SO2 have significant adverse effects on man, plants and other animals. There is a need for regular monitoring of their levels in the atmosphere. In this study, the concentrations of three gaseous air pollutants (SO2, NOx and NH3) emitted from municipal solid waste at Ajakanga dump site, Ibadan, Nigeria, were determined using uv/visible spectrophotometry. The ranges of concentrations obtained for SO2, NOx and NH3 were 255.86–503.66 µg/m3 ; 246.67–1,155.79 µg/m3 and 777.51–1,852.48 µg/m3 respectively in air samples collected at the dump site. The increasing order of the gaseous air pollutants at the dump site is SO2 < NOx < NH3. The emission rates of SO2, NOx and NH3 must be controlled because of their adverse health effects on the environment.